2020
DOI: 10.2147/cmar.s273065
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative Fibrinogen-Albumin Ratio Index (FARI) is a Reliable Prognosis and Chemoradiotherapy Sensitivity Predictor in Locally Advanced Rectal Cancer Patients Undergoing Radical Surgery Following Neoadjuvant Chemoradiotherapy</p>

Abstract: Background Inflammatory response and nutritional status are associated with cancer development and progression. The purpose of this study was to explore whether the preoperative fibrinogen-albumin ratio index (FARI) is related to prognosis and chemoradiotherapy outcome of radical surgery after neoadjuvant chemoradiotherapy (NCRT) in patients with locally advanced rectal cancer (LARC). Methods In total, 123 patients with LARC who underwent radical surgery after NCRT betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
5
16
1
Order By: Relevance
“…However, NCRT may reduce the total circulating leukocytes and interfere with the in ammatory response of the host, limiting the application of leukocyte-based in ammation biomarkers to predict the prognosis of LARC patients who underwent NCRT [17]. Our previous ndings were consistent with this point of view [20]. The CFP scoring system is a combination of tumor markers (CEA), in ammatory factors (lymphocytes and brinogen), and nutritional factors (albumin).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…However, NCRT may reduce the total circulating leukocytes and interfere with the in ammatory response of the host, limiting the application of leukocyte-based in ammation biomarkers to predict the prognosis of LARC patients who underwent NCRT [17]. Our previous ndings were consistent with this point of view [20]. The CFP scoring system is a combination of tumor markers (CEA), in ammatory factors (lymphocytes and brinogen), and nutritional factors (albumin).…”
Section: Discussionsupporting
confidence: 78%
“…The brinogen-toalbumin index (FARI) is considered an essential biomarker that re ects both systemic in ammatory status and nutritional status, and several studies have reported that FARI is closely related to the prognosis of various cancers, such as breast cancer [17], esophageal cancer [18], and gastric cancer [19]. Our previous ndings have shown similar results in LARC patients undergoing TME following NCRT, and we have found that FARI is associated with tumor response [20]. The prognostic nutritional index (PNI), based on the albumin level and lymphocyte count, is another widely used biomarker that combines in ammatory and nutritional parameters.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Their expression levels correlate with the therapeutic effects of radiotherapy and chemotherapy. 15 , 16 , 18 , 65 , 97–105 In recent years, an increasing number of scholars have highlighted the application value of FPR and FAR or AFR in colorectal cancer treatment. The detection of serum levels of FPR and FAR or AFR is not only suitable for CRC patients with AJCC diagnosed as being stage I–III but also for high-risk patients with metastasis.…”
Section: Application Of Fpr and Far Or Afr In Crcmentioning
confidence: 99%